Clinical outcomes of patients with and without chronic kidney disease undergoing endovascular revascularization of infrainguinal peripheral artery disease: Insights from the XLPAD registry. Issue 2 (1st February 2021) - Kabir, Ryan; Vuppala, Suchith; Liu, Yulun; Tejani, Ishita; Weideman, Rick; Banerjee, Avantika; Tsai, Shirling; Huffman, Lynn; Niazi, Khusrow; Brilakis, Emmanouil S.; Shishehbor, Mehdi H.; Banerjee, Subhash
Abstract: Objectives: The purpose of the present study was to define clinical outcomes of chronic kidney disease (CKD) patients undergoing endovascular revascularization of infrainguinal peripheral artery disease (PAD). Background: CKD is an established predictor of advanced PAD. However, clinical outcomes for these patients following endovascular revascularization remain inadequately defined. Methods: Using the ongoing multicenter Excellence in Peripheral Artery Disease (XLPAD) registry (NCT01904851), we analyzed all‐cause death, target limb amputation, and need for repeat revascularization for patients with and without CKD undergoing infrainguinal endovascular revascularization between the years 2005 and 2018. Results: Of 3, 699 patients, 15.1% ( n = 559) had baseline CKD. CKD patients had significantly higher incidence of heavily calcified lesions (48.4% vs. 38.1%, p < .001) and diffuse disease (66.9% vs. 61.5%, p = .007). Kaplan–Meier analysis showed significant differences between CKD and non‐CKD patient outcomes at 12 months for freedom from target limb amputation (79.9% vs. 92.7%, p < .001) and all‐cause death (90.1% vs. 97.6%, p < .001). However, freedom from target vessel revascularization was similar between the groups. After adjusting for baseline comorbidities in the CKD and non‐CKD groups, the hazard ratios for target limb amputation and death at 12 months were 2.28 (95% confidence interval or CI 1.25–4.17, p < .001) and 4.38 (95% CI 2.58–7.45, p < .001), respectively. Conclusions: Following endovascular revascularization for infrainguinal PAD, CKD was an independent predictor of all‐cause death and target limb amputation at 12 months.